Effects of Long-Term Environmental Enrichment on Anxiety, Memory, Hippocampal Plasticity and Overall Brain Gene Expression in C57BL6 Mice - Hüttenrauch, Melanie; Salinas, Gabriela; Wirths, Oliver (Frontiers in Molecular Neuroscience, 2016)
There is ample evidence that physical activity exerts positive effects on a variety of brain functions by facilitating neuroprotective processes and influencing neuroplasticity. Accordingly, numerous studies have shown that continuous exercise can successfully diminish or prevent the pathology of neurodegenerative diseases such as Alzheimer’s disease in transgenic mouse models. However, the long-term effect of physical activity on brain health of aging WT mice has not been studied in detail yet. Here, we show that prolonged physical and cognitive stimulation, mediated by an enriched environment (EE) paradigm for a duration of eleven months, leads to reduced anxiety and improved spatial reference memory in C57BL6 wildtype (WT) mice. While the number of CA1 pyramidal neurons remained unchanged between standard housed (SH) and EE mice, the number of dentate gyrus (DG) neurons, as well as the CA1 and DG volume were significantly increased in EE mice. A whole-brain deep sequencing transcriptome analysis, carried out to better understand the molecular mechanisms underlying the observed effects, revealed an up-regulation of a variety of genes upon EE, mainly associated with synaptic plasticity and transcription regulation. The present findings corroborate the impact of continuous physical activity as a potential prospective route in the prevention of age-related cognitive decline and neurodegenerative disorders.